In search of a conservation ethic - Salim, A.; Brocklesby, M.A.; Tiani, A.M.; Tchikangwa, B.; Sardjono, M.A.; Porro, R.; Woelfel, J.; Colfer, C.J.P. (Resources for the Future and Center for International Forestry Research, 2001)
This paper makes use of the Galileo method to compare cognitive distances between selected forest-related concepts in Brazil, Indonesia and Cameroon. The purpose is to determine whether or not there are significant differences in people’s perceptions that could reflect the concept of a conservation ethic in these locations. Specific hypotheses focus on the cognitive relationships between spirit and forest; between forest, good and future; and between forest and me. Although the method provides interesting and useful information on cognition, it is less useful in clarifying the existence or measurement of a conservation ethic.